Promoting virtual, informal learning now to thrive in a post‐pandemic world. (8th March 2022) - Zajac, Stephanie; Randall, Jason; Holladay, Courtney
Abstract: A significant practical and ethical challenge that societies, governments, and organizations face in response to COVID‐19 is how to support individual learning and development during times of operational challenge. We address two key challenges the pandemic poses to learning. First, safety measures to mitigate the virus' spread closed physical spaces where most learning traditionally occurs, and significant portions of the workforce have moved to remote work. Taken together, this requires learning to be virtual. Second is how the shift to virtual or hybrid working structures impacts the inherently social nature of learning at work and particularly of informal learning. Thus, as society grapples with ways of supporting student learning, we must not neglect organizations' role in supporting virtual, informal employee learning during the COVID‐19 pandemic and beyond as remote work becomes the new normal. Toward this end, we present five tips to promote informal learning in a virtual world to preserve the socially supported, continuous learning required for an agile workforce post‐pandemic. Tips provide actionable advice on how to create spontaneous connection, support virtual mentoring, be inclusive in offering developmental activities, capture lessons learned, and create a culture of lifelong learning. Future research directions for virtual, informal learning are provided.